1993
DOI: 10.1080/02652039309374161
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Canadian and imported beers forFusariummycotoxins by gas chromatography—mass spectrometry

Abstract: A sensitive method was developed for the determination of deoxynivalenol (DON), nivalenol (NIV), alpha-zearalenol (alpha-ZEL), beta-zearalenol (beta-ZEL) and zearalenone (ZEN) in beer by capillary gas chromatography-mass spectrometry (GC-MS) of their heptafluorobutyrate (HFB) derivatives. Recoveries averaging 90-103% were obtained from beers spiked with each mycotoxin in the 5-20 ng/ml concentration range. Limits of detection were 0.1-1.5 ng DON/ml, 0.01-0.3 ng NIV/ml, 2.5-3 ng alpha- and beta-ZEL/ml, and 1.5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 12 publications
0
38
0
4
Order By: Relevance
“…As far as we know analysis methods reported in the literature for DON level in beer were TLC (Odhav & Naicker, 2002;Trucksess, Flood, & Page, 1986), gas chromatography with electron-capture detection, flame ionisation detection or mass spectrometry (Molto et al, 2000;Schothorst & Jekel, 2003;Schothorst & van Egmond, 2004;Scott, Kanhere, & Weber, 1993;Shim, Kim, Seo, & Lee, 1997), enzyme-linked immunosorbent assay (Niessen, Böhm-Schrami, Vogel, & Donhauser, 1993;Papadopoulou-Bouraoui et al, 2004;Ruprich & Ostry, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…As far as we know analysis methods reported in the literature for DON level in beer were TLC (Odhav & Naicker, 2002;Trucksess, Flood, & Page, 1986), gas chromatography with electron-capture detection, flame ionisation detection or mass spectrometry (Molto et al, 2000;Schothorst & Jekel, 2003;Schothorst & van Egmond, 2004;Scott, Kanhere, & Weber, 1993;Shim, Kim, Seo, & Lee, 1997), enzyme-linked immunosorbent assay (Niessen, Böhm-Schrami, Vogel, & Donhauser, 1993;Papadopoulou-Bouraoui et al, 2004;Ruprich & Ostry, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…As novas tendências para detecção de micotoxinas em bebidas apontam o emprego de colunas de imunoafinidade para extração e limpeza [23,24,32], mas esta técnica quando comparada com o método proposto tem como desvantagem o alto custo, a possibilidade de falsos positivos e a não detecção de várias toxinas simultaneamente.…”
Section: -Eficiência Do Métodounclassified
“…Until recently, analytical methodology for the determination of DON in beer relied predominantly on gas chromatography (GC) coupled either with conventional detection such as electron capture detector (ECD) (Molto et al ., 2000), flame ionization detector (FID) (Schothorst and Jekel, 2003) or mass spectrometry (MS) (Scott et al ., 1993, Bertuzzi et al ., 2011 . Liquid chromatography hyphenated to spectrophotometric detection (LC-UV) has been used to a lesser extent (Anselme et al ., 2006;Balajová and Rauová, 2008;Omurtag and Beyoğlu, 2007) .…”
Section: Instrumental Analytical Methodsmentioning
confidence: 99%
“…In addition, extensive clean-up is important in order to remove matrix components reacting with the derivatization agent, interfering in final analysis or both . A two-step clean-up first on a cartridge with a hydrophilic stationary phase, then on a C18-cartridge was employed in a GC-MS method for the determination of DON along with nivalenol (NIV), zearalenone (ZEA), α-zearalenol and β-zearalenol in beer (Scott et al ., 1993) . In that study it was shown that heptafluorobutyric (HFB) derivatization resulted in a better sensitivity than derivatization with trimethylsilylation (TMS) .…”
Section: Gas Chromatographymentioning
confidence: 99%